Identification of distinct disease activity trajectories in patients with psoriatic arthritis receiving tofacitinib: a post hoc analysis of two phase 3 studies - Laura C Coates; Dafna Gladman; Mikhail Volkov; David Gruben; William Tillett; Stefanie Hahne (RMD Open)
Objective To capture variations in tofacitinib treatment response in psoriatic arthritis (PsA) by identifying patient groups with distinct disease activity trajectories.Methods Data were pooled post hoc from two phase 3 studies (OPAL Broaden, OPAL Beyond) in patients with PsA receiving tofacitinib 5 or 10 mg twice daily (n=225, n=226, respectively). Psoriatic Arthritis Disease Activity Score (PASDAS) to month 6 was used in group-based trajectory modelling to identify distinct treatment response groups based on disease state (very low/low/moderate/high disease activity (VLDA/LDA/MoDA/HDA, respectively)). Baseline characteristics, PASDAS components to month 6 and adverse events (AEs) were assessed.Results Five trajectory groups were identified for both tofacitinib doses: groups improved from MoDA→VLDA/LDA (group 1); HDA→VLDA (group 2); HDA→MoDA rapidly (group 3) or gradually (group 4) or remained in HDA (group 5). Groups 4/5 generally had significantly higher baseline PsA clinical domain scores than groups 1‒3, except for Psoriasis Area and Severity Index/Nail Psoriasis Severity Index. Baseline Leeds Enthesitis Index/Spondyloarthritis Research Consortium of Canada enthesitis scores and tender joint counts were significantly higher in group 4 vs group 2. PASDAS components generally improved to month 6 in all groups, consistent with modelled trajectories. There were no clear trends in AEs across groups.Conclusions In patients with PsA receiving tofacitinib, five distinct trajectory groups were identified with different baseline characteristics and treatment outcomes, but no clear trends in AEs. The tofacitinib 5 and 10 mg twice daily models showed comparable trajectories and baseline characteristics. In patients with HDA, enthesitis and tender joint count may impact timing and/or magnitude of response to tofacitinib. Identifying characteristics that impact treatment response may aid personalised treatment algorithm development.Trial registration numbers NCT01877668/NCT01882439.